Impact of KRAS G12C mutation on the efficacy of chemoradiotherapy in patients with unresectable stage II or III non-small cell lung cancer - Cabon, Jean; Lerouge, Delphine; Thureau, Sebastien; Balosso, Jacques; Guigo, Marin; Gervais, Radj; Dubos, Catherine; Dô, Pascal; Demontrond, Pierre; Curcio, Hubert; Deshayes, Simon; Madelaine, Jeannick; et al. (Frontiers in Oncology, 2025)
BackgroundApproximately 35% of patients with non-small cell lung cancer (NSCLC) have locally advanced disease. Despite treatment with chemoradiotherapy (CRT) and consolidation immunotherapy, overall survival remains below 50% at 5 years. Kirsten rat sarcoma (KRAS) mutations (KRASms) are the most common lung cancer mutations, affecting 25% of NSCLC cases. KRASm can cause radioresistance, and several targeted KRASm therapies have been developed, mainly targeting the KRAS G12C mutation (KRASm G12C), but the impact of KRASm G12C on the efficacy of CRT for locally advanced NSCLC remains unclear.MethodsWe conducted a multicenter retrospective study of unresectable stage II or III NSCLC treated with CRT in four French hospitals between January 2014 and December 2022. The primary endpoint was the objective response rate (ORR) for KRASm G12C compared to KRAS wild-type (KRASwt). The main secondary objectives were to assess the difference in ORR between KRASm and KRASwt, and the difference in disease control rate (DCR), overall survival (OS), progression-free survival (PFS), time to local relapse (TTLR), and time to distant relapse (TTDR) according to KRASm status.ResultsOur study included 267 patients, and 73 patients had KRASm (27.3%). The most common KRASm was KRASm G12C (n = 42). Tumors were lung adenocarcinoma in 91% (n = 244) of patients. Two hundred (75%) patients were treated with concomitant CRT. There was no difference between KRASm G12C and KRASwt patients in terms of ORR (48% vs. 49%; p = 0.961) and DCR (86% vs. 84%; p = 0.903), nor when comparing KRASm to KRASwt in terms of OS (p = 0.64), PFS (p = 0.28), TTLR (p = 0.26), and TTDR (p = 0.3), with no impact after adjustment for durvalumab.ConclusionKRAS G12C mutation compared to KRAS wild-type did not affect response to chemoradiotherapy, and KRAS mutations compared to KRAS wild-type were not associated with worse survival in unresectable stage II or III NSCLC treated with chemoradiotherapy.